Pokémon : Race to Danger [anglicky]. Book 5 - West, Tracey, 1965- (Orchard Books, 2021)
Pokémon master-in-training Ash Ketchum is facing a brand-new challenge - a hot air balloon battle!Ash and his friends must race the other Pokémon trainers to catch a rare Dratini, before Team Rocket shoots them down! Can Ash get everyone back down safely - and still get his hands on first prize?